Art, performance and ritual in Benin City - Gore, Charles (Charles D.) (International African library, 2007)
This book explores the roles of contemporary urban shrines and their visual traditions in Benin City. It focuses on the charismatic priests and priestesses who are possessed by a pantheon of deities, the communities of devotees, and the artists who make artifacts for their shrines. The visual arts are part of a wider configuration of practices that include song, dance, possession and healing. These practices provide the means for exploring the relationships of the visual to both the verbal and performance arts that feature at these shrines. The analysis in this book raises fundamental questions about how the art of Benin, and non-Western art histories more generally, are understood. The book throws critical light on the taken-for-granted assumptions which underpin current interpretations and presents an original and revisionist account of Benin art history.